Clave para la determinación de las especies de mojarras de México (Pisces: Gerreidae) - Tapia-García, M.; Ayala-Pérez, G. (Revista de Biología Tropical, 1996)
There are five genera and 20 species of Ihe family Gerreidae in Mexican coastal waters. Eleven species occur in the Gulf of Mexico and the Mexican caribbean Sea. and len species are distributed in the Méxican Pacific. Guerreids have presented some taxonomic and nomenclatural problems (mainly Eucinostomus). This up-to-dale general key to Mexican gerreids includes illustrations for the 20 known species.